The Role of Safety Awareness in Mediating the Effect of Leadership on Operational Safety at PT Kereta Api Indonesia (Persero) Regional Division I North Sumatra - Ikhlas Sirait, Ibnu; Toyib Daulay, Muhammad; Kholik, Kholilul (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to identify and analyze the role of safety awareness in mediating the influence of leadership on operational safety at PT Kereta Api Indonesia (Persero) Regional Division I, North Sumatra. This study is motivated by the importance of operational safety in railway activities, which involve human resources, facilities, infrastructure, procedures, and safety management systems. Leadership is a key factor in promoting safe work behavior, while safety awareness plays a role in fostering employees’ ability to recognize potential hazards, understand risks, and take preventive actions. This study employs a quantitative approach. The population consists of 609 employees in the operational units of PT Kereta Api Indonesia (Persero) Regional Division I, North Sumatra. The sample comprises 86 respondents, determined using the Slovin formula. The sampling technique used was purposive sampling, and data were collected through the distribution of a questionnaire using a Likert scale. The data analysis technique used was Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of the SmartPLS 3.0 program. The results of the study indicate that leadership has a positive and significant effect on operational safety, with a coefficient value of 0.239, a t-statistic value of 3.509, and a p-value of 0.000. Leadership also has a positive and significant effect on safety awareness, with a coefficient of 0.363, a t-statistic of 5.977, and a p-value of 0.000. Furthermore, safety awareness has a positive and significant effect on operational safety, with a coefficient of 0.364, a t-statistic of 4.556, and a p-value of 0.000. The results of the indirect effect test indicate that safety awareness mediates the effect of leadership on operational safety, with a coefficient of 0.132, a t-statistic of 3.607, and a p-value of 0.000.